2018
DOI: 10.3892/ol.2018.8730
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of mRNA‑decapping enzyme 1a affects survival rate in colorectal carcinoma

Abstract: Abstract. Processing bodies (P-bodies) are one of the most well understood types of RNA granules, and are associated with a variety of diseases, including cancer. mRNA-decapping enzyme 1a (DCP1a), which may be used as a marker to analyze P-bodies, participates in the removal of the 5'-methylguanosine cap from eukaryotic mRNAs as a cofactor. The aim of the present study was to analyze the association between DCP1a expression and clinical features in colorectal carcinoma (CRC). The levels of DCP1a mRNA expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In addition, Tang, Y. 's study found that the high expression of DCP1A in colorectal carcinoma is correlated with poor prognosis [57], which is consistent with our results, indicating that the other PCGs and lncRNAs in our results could also be prognostic indicators for NFPA.…”
Section: Am J Biomed Sci and Ressupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, Tang, Y. 's study found that the high expression of DCP1A in colorectal carcinoma is correlated with poor prognosis [57], which is consistent with our results, indicating that the other PCGs and lncRNAs in our results could also be prognostic indicators for NFPA.…”
Section: Am J Biomed Sci and Ressupporting
confidence: 91%
“…These studies indicated that MOV10 could be critical in tumorigenesis. DCP1A is a protein-coding gene for mRNA-decapping enzyme 1a, and several studies have revealed that DCP1A is upregulated in tumour tissues such as malignant melanoma, colorectal carcinoma and gastric cancer [56][57][58]. In addition, Tang, Y.…”
Section: Am J Biomed Sci and Resmentioning
confidence: 99%
“… 21 , 22 Studies have shown that DCP1A expression is up-regulated in CRC, and its elevated expression is associated with the reduced survival rate in CRC patients. 23 , 24 Therefore, it may be a key target to regulate CRC progress.…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that MOV10 could be critical in tumorigenesis. DCP1A is a protein-coding gene for mRNA-decapping enzyme 1a, and several studies have revealed that DCP1A is upregulated in tumor tissues, such as malignant melanoma, colorectal carcinoma and gastric cancer (67)(68)(69). In addition, Tang et al (67) and Wu et al (68) reported that the high expression of DCP1A in colorectal carcinoma is correlated with poor prognosis, which is consistent with the current results, thus indicating that the other present PCGs and lncRNAs could also be prognostic indicators for NFPA.…”
Section: Discussionmentioning
confidence: 99%